A Monte Carlo study on 223Ra imaging for unsealed radionuclide therapy. Issue 6 (30th November 2016) - Takahashi, Akihiko; Miwa, Kenta; Sasaki, Masayuki; Baba, Shingo
Abstract : Purpose: Radium‐223 ( 223 Ra), an α‐emitting radionuclide, is used in unsealed radionuclide therapy for metastatic bone tumors. The demand for qualitative 223 Ra imaging is growing to optimize dosimetry. The authors simulated 223 Ra imaging using an in‐house Monte Carlo simulation code and investigated the feasibility and utility of 223 Ra imaging. Methods: The Monte Carlo code comprises two modules, hexagon andnai . Thehexagon code simulates the photon and electron interactions in the tissues and collimator, and thenai code simulates the response of the NaI detector system. A 3D numeric phantom created using computed tomography images of a chest phantom was installed in thehexagon code. 223 Ra accumulated in a part of the spine, and three x‐rays and 19 γ rays between 80 and 450 keV were selected as the emitted photons. To evaluate the quality of the 223 Ra imaging, the authors also simulated technetium‐99m ( 99m Tc) imaging under the same conditions and compared the results. Results: The sensitivities of the three photopeaks were 147 counts per unit of source activity (cps MBq −1 ; photopeak: 84 keV, full width of energy window: 20%), 166 cps MBq −1 (154 keV, 15%), and 158 cps MBq −1 (270 keV, 10%) for a low‐energy general‐purpose (LEGP) collimator, and those for the medium‐energy general‐purpose (MEGP) collimator were 33, 13, and 8.0 cps MBq −1, respectively. In the case of 99m Tc, the sensitivity was 55 cps MBq −1 (141 keV, 20%) for LEGP and 52 cps MBq −1 for MEGP. The fractions of unscattered photons of the total photons reflecting the image quality were 0.09 (84 keV), 0.03 (154 keV), and 0.02 (270 keV) for the LEGP collimator and 0.41, 0.25, and 0.50 for the MEGP collimator, respectively. Conversely, this fraction was approximately 0.65 for the simulated 99m Tc imaging. The sensitivity with the LEGP collimator appeared very high. However, almost all of the counts were because of photons that penetrated or were scattered in the collimator; therefore, the proportions of unscattered photons were small. Conclusions: Their simulation study revealed that the most promising scheme for 223 Ra imaging is an 84‐keV window using an MEGP collimator. The sensitivity of the photopeaks above 100 keV is too low for 223 Ra imaging. A comparison of the fractions of unscattered photons reveals that the sensitivity and image quality are approximately two‐thirds of those for 99m Tc imaging.